2001
DOI: 10.1104/pp.125.3.1258
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Better Understanding of the Genetic and Physiological Basis for Nitrogen Use Efficiency in Maize

Abstract: To enhance our understanding of the genetic basis of nitrogen use efficiency in maize (Zea mays), we have developed a quantitative genetic approach by associating metabolic functions and agronomic traits to DNA markers. In this study, leaves of vegetative recombinant inbred lines of maize, already assessed for their agronomic performance, were analyzed for physiological traits such as nitrate content, nitrate reductase (NR), and glutamine synthetase (GS) activities. A significant genotypic variation was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
296
3
9

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 442 publications
(319 citation statements)
references
References 48 publications
11
296
3
9
Order By: Relevance
“…A variabilidade genética para a atividade da glutamina sintetase (GS) bem como a sua correlação com a EUN têm sido demonstradas em vários estudos (Denbinski et al 1991, Lam et al 1995, Reggiani et al 1999, Hirel et al 2001. Denbinski et al (1991) verificaram que a seleção para alto teor protéico em milho foi acompanhada pelo incremento da atividade da GS no endosperma.…”
Section: Introductionunclassified
“…A variabilidade genética para a atividade da glutamina sintetase (GS) bem como a sua correlação com a EUN têm sido demonstradas em vários estudos (Denbinski et al 1991, Lam et al 1995, Reggiani et al 1999, Hirel et al 2001. Denbinski et al (1991) verificaram que a seleção para alto teor protéico em milho foi acompanhada pelo incremento da atividade da GS no endosperma.…”
Section: Introductionunclassified
“…the HATs system) are up-regulated by N shortage in the soil or feedback-regulation depending upon the shoots' demand for N (Wirén et al 1997;Forde 2002). Moreover, both processes-N uptake and N utilization-appear to be governed by different genetic factors (Hirel et al 2001;Gallais and Hirel 2004;Good et al 2004). For instance, results of extensive molecular studies on wheat and maize Gallais 2000, 2001;Quarrie et al 2005;Habash et al 2007;Laperche et al 2007) revealed that different sets of genes (QTL regions) controlled various components of the two major measures of N efficiency, and that expression of the genes (loci) was considerably dependent upon soil N status.…”
Section: Combining Ability Effectsmentioning
confidence: 99%
“…NUE is a quantitative plant trait with a polygenic inheritance, which is influenced by N availability (Hirel et al 2001). The latter is difficult to control under field conditions (Fageria and Baligar 2005) and this will complicate genetic analysis of NUE variation.…”
Section: Introductionmentioning
confidence: 99%